IMPROVED PHOTOMETRIC CHARACTERISTICS OF THE NEWLY DISCOVERED EW-TYPE SYSTEM GSC 04370-00206 - Breus, V. V.; Andronov, I. L.; Dubovsky, P. A.; Hegedus, T.; Kudzej, I.; Petrik, K. (Одеські астрономічні публікації, 2010)
We present results of two-color photometric study of the newly discovered EW– type eclipsing binary star GSC 04370-00206 in the field of the intermediate polar MU Cam. CCD V,R observations were obtained in the Astronomical Observatories in Hlohovec, Baja and Kolonica in 2007-2009. Improved photometric elements for the primary minimum were determined: Min.BJD=2454805.75635+0.44264511(27)E. The range of the brightness variations is 13.79-14.13 (V) and 13.07-13.44 (R). The accuracy of the period determination is by a factor of ∼ 7, 000 times better than the one published by the discoverers based on only one night of observations. We report on the night-to-night variability of the shape of the light curve which is interpreted by a presence of spots in the atmosphere of one or both components (O’Connel effect).